Playing with method: testing one approach towards identifying the places of past children. (14th December 2021) - Cory, Mackenzie
Abstract: Abstract: Before approaching larger questions surrounding the role of children as agents of innovation in the past, we must first be able to confidently archaeologically identify their presence within social spaces. While previous research has broken down some assumptions surrounding the use of material culture by children, there still exists a considerable gap in the identification of features relating to children's activities in the archaeological record. The identification of play areas at archaeological sites contributes to a better understanding of the artefacts located in proximity to them, increasing the accuracy of interpretations of the past. This paper presents a possible methodological solution to identifying children's spaces in the archaeological record of North America's Northwest Plains. The historic record indicates that Indigenous children engaged in domestic play using several varieties of play tipis, some of which have potential to be identified in the archaeological record as small stone circles. I examine if there is any significant difference between stone circles possibly representing play areas from those representing hearths based on the feature attributes identified from archival collections. Analysis of these features from nine Wyoming counties reveals significant differences between hearths and play tipis.